Development Of Interactive Digital Media On Single Data Presentation Materials For Class IV Sdn Jatayu Bandung - Imas Masitoh (Universitas Maritim AMNI Semarang, 2023)
Difficulty of students in understanding the material, as well as the difficulty of teachers to explain the material in the process of learning Mathematics due to the use of learning media or limited teaching materials, in addition to the lack of use of digital learning media that varies resulted in the learning process of mathematics performed by teachers with students is less than maximum. The research is aimed at developing interactive digital media based on E-Book on Class IV Mathematics subjects, using the Borg and Gall model research and development (R&D) method modified by Sugiyono to solve problems as well as to be an alternative for teachers and students in the learning process of mathematics in SD and to know the validity of products that have been developed through the Stage of Material Validation and Media validation. The Borg and Gall model, modified by Sugiyono, consists of five stages of development: potential and problems, information collection, product design, design validation, and design revision